Impact of Coping Strategies on the Academic Satisfaction of University Students and Their Association with Socioeconomic Variables - Ana Dorado Barbé; David González Casas; Linda V. Ducca Cisneros; Jesús M. Pérez Viejo (Psicología Educativa: Revista de los Psicólogos de la Educación)

(untitled)
Conflict situations in higher education settings often lead to high stress levels among university students. Coping strategies are crucial in students’ educational experiences and academic satisfaction. This study aimed to analyse the coping strategies in conflict situations and their correlation with social and academic variables in Complutense University of Madrid (UCM) students. A study employing both qualitative and quantitative approaches, using data triangulation, was conducted through online surveys distributed to 2,803 students, along with six focus group sessions. The findings indicate that appropriate coping strategies are positively associated with academic satisfaction and mediation training. Female university students tend to use emotion-focused coping strategies more frequently, whereas students at lower academic levels tend to use avoidant coping strategies more often. Understanding and investigating the relationship between coping strategies and socio-academic variables can aid in implementing educational policies to enhance students’ personal resources and academic experiences in higher education.